Best Answer

y=b+x+x^2 This is a quadratic equation. The graph is a parabola. The quadratic equation formula or factoring can be used to solve this.

Q: Y equals b plus x plus x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

For a quadratic equation y=Ax2+Bx+C, the line of symmetry is given by x=-B/2ASo for the equation y=-x2+x+3, B is 1 and A is -1, so the line of symmetry isx=1/2

y = x2 + 8x - 7 a = 1, b = 8, c = -7 the equation of the axis of symmetry: x = -b/2a x = -8/(2*1) = -4

The value of m is the slope and the value of b is the y intercept.

The graph of the equation is a straight line. 'm' is its slope. 'b' is its y-intercept

That depends on the values of m and b because it is the formula for a straight line equation whereas m is the slope and b is the y intercept

Related questions

y = x2 + 14x + 21 a = 1, b = 14 x = -b/2a = -14/2*1 = -7

a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z

y = x2 + 14x + 21; a = 1, b = 14, c = 21 x-coordinate = -b/2a = -14/2 = -7 if it is y = x2 + 14 + 21, the x-coordinate is zero, since b = 0.

in order to solve this problem you have to solve for x first wich you are given the data to pre forme so x=4 and x.2=8 and 8=y and y-4=4=a=x so a+8=12 and 12=b

in the equation: y=mx+b , the y-intercept is represented by "b".

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

If: A = Y+B Then: -Y = -A+B or Y = A-B

For a quadratic equation y=Ax2+Bx+C, the line of symmetry is given by x=-B/2ASo for the equation y=-x2+x+3, B is 1 and A is -1, so the line of symmetry isx=1/2

y = x2 + 8x - 7 a = 1, b = 8, c = -7 the equation of the axis of symmetry: x = -b/2a x = -8/(2*1) = -4

Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y

same thing. but its easy to change y=b+mx to y=mx+b

y=x2+2x+1 -b -2 2a= 2= -1 = axis of symmetry is negative one.